PENGARUH BUDAYA ORGANISASI DAN SELF-ESTEEM TERHADAP PRESTASI GURU SMP NEGERI DI WILAYAH JAKARTA TIMUR - Windi Megayanti (Jurnal Manajemen Pendidikan, 2018)
The purpose of this research is to know the effect of organizational culture and self-esteem toward teacher’s achievement junior high school in east of Jakarta.The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 200 teachers. Research samples selected as much as 133 teachers using proportional random sampling technique. The data obtained through questionnaires and analyzed using path analysis techniques. Based on the results of data analysis in this research it is concluded: (1) the organizational culture have positive direct effect to achievement; (2) the self-esteem have positive direct effect to achievement; (3) the organizational culture have positive direct effect to self-esteem. The achievement can be improved through improvement of organizational culture and self-esteem